circMELK promotes glioblastoma multiforme cell tumorigenesis through the miR-593/EphB2 axis - Fengqi Zhou; Binbin Wang; Hong Wang; Lang Hu; Junxia Zhang; Tianfu Yu; Xiupeng Xu; Wei Tian; Chunsheng Zhao; Haifeng Zhu; Ning Liu (Elsevier, 2021)
A number of studies indicate that circular RNAs (circRNAs) play paramount roles in regulating the biological behavior of glioblastoma multiforme (GBM). In this study, we investigated the underlying mechanism of circMELK in GBM. Real-time PCRs were used to examine the expression of circMELK in glioma tissues and normal brain tissues (NBTs). Localization of circMELK in GBM cells was estimated by fluorescence in situ hybridization (FISH). Transwell migration and three-dimensional invasion assays were performed to examine glioma cell migration and invasion in vitro. Spheroid formation, clonogenicity, and cell viability assays were implemented to test the stemness of glioma stem cells (GSCs). The functions of circMELK in vivo were investigated in a xenograft nude-mouse model. We have proved that circMELK functions as a sponge for tumor suppressor microRNA-593 (miR-593) by RNA immunoprecipitation and circRNA precipitation assays, which targets the oncogenic gene Eph receptor B2 (EphB2). Dual-luciferase reporter assays were adopted to estimate the interactions between miR-593 and circMELK or EphB2. We demonstrated that circMELK was upregulated in GBM, acting as an oncogene and regulating GBM mesenchymal transition and GSC maintenance via sponging of miR-593. Furthermore, we found that EphB2 was involved in circMELK/miR-593 axis-induced GBM tumorigenesis. This function opens the opportunity for the development of a novel therapeutic target for the treatment of gliomas.